The influence of left ventricular geometry on left atrial phasic function in hypertensive patients. (2nd November 2015) - Tadic, Marijana; Cuspidi, Cesare; Pencic, Biljana; Kocijancic, Vesna; Celic, Vera
Abstract : Objective . We aimed to investigate left atrial (LA) phasic function in hypertensive patients with different geometric patterns using two-dimensional (2DE) and three-dimensional (3DE) echocardiography. Methods . This cross-sectional study included 213 hypertensive subjects who underwent a complete 2DE and 3DE examination. The new updated criteria for left ventricular (LV) geometry, which consider LV mass index, LV end-diastolic diameter and relative wall thickness, were applied. According to this classification, the subjects were divided into six groups: normal geometry, concentric remodeling, eccentric non-dilated left ventricular hypertrophy (LVH), concentric LVH, dilated LVH and concentric-dilated LVH. Results . 2DE and 3DE LA volumes gradually increased from normal LV geometry to concentric and concentric-dilated LVH. LA reservoir and conduit functions, estimated by 2DE and 3DE LA total and passive emptying fractions, were decreased in subjects with concentric and concentric-dilated LVH. LA booster pump function was increased in patients with concentric, dilated and concentric-dilated LVH compared to subjects with normal LV geometry. The same results regarding LA phasic function were provided by 2DE strain analysis. Concentric, dilated and non-concentric dilated LVH were associated with LA enlargement independently of main demographic and clinical features. Conclusion . LV geometric patterns significantly influence LA phasic function. Concentric and dilated LVH patterns have the most prominent negative effect on LA enlargement assessed by both 2DE and 3DE.